REDEFINING LOCAL GOVERNMENT WITHIN THE MACRO-DEVELOPMENT AGENDA IN SOUTH AFRICA - Kgobe, France Khutso Lavhelani; Mamokhere, John (Journal of Social Political Sciences, 2025)
The Constitution of the Republic of South Africa, 1996, promotes local government as an autonomous sphere, but hierarchical political arrangements and party structures have weakened this, leading to a weakening of local voices. Local government is crucial for providing essential services like water, electricity, housing, and infrastructure development, aiming to bridge the gap between wealthy and disadvantaged communities and improve the quality of life. However, South Africa's local governments face numerous challenges in service delivery, including bureaucratic inefficiencies, insufficient resources, and systemic corruption, which hinder their ability to provide essential services to these communities. This study carefully explores the evolving role of local government within South Africa's macro-development agenda, focusing on the challenges of service delivery and the reforms in governance. It is grounded in three fundamental theoretical perspectives: the Democratic Participatory School, which underlines the importance of local government in promoting citizen engagement and accountability; the Efficiency Services School, which regards local governance as a means for effective and responsive service provision; and the Development School, which sees local government as a catalyst for socio-economic development and transformation. The study employs a qualitative research approach. The study explores the governance structures, policies, frameworks, and service delivery outcomes. The data collection emanates from secondary sources, including governmental reports, policy documents, and scholarly publications. The data is analysed thematically to uncover key service delivery challenges. In the quest to improve service delivery in South Africa, the study welcomes the proposed revision of the 1998 white paper on local government as a robust and decisive approach to strengthen service delivery outcomes. The study believes that revising the 1998 White Paper on Local Government presents a crucial opportunity to enhance service delivery in South Africa by addressing systemic challenges that have hindered municipal effectiveness over the past 30 years. A refreshed policy framework can improve the responsiveness of local governments, ensuring the timely and efficient provision of essential services such as water, sanitation, and electricity. The study further recommends the necessity for improved intergovernmental collaboration, increased stakeholder participation in municipal affairs, and capacity building within institutions to enhance governance effectiveness and ensure sustainable service delivery. The study concludes that it is crucial to reposition local government within the broader context of the national development strategy to achieve long-term socio-economic advancement.